The Influence of Mobile Marketing and Content Marketing on Shopee User Customer Engagement in Sukabumi City - Hastuti, Ledi Sri (PT Inovasi Pratama Internasional, 2023)
This study aims to analyze and explain mobile marketing and content marketing in influencing customer engagement. The research method used in this study is associative with a quantitative approach. The sample in the study was 100 Shopee user consumers. The research data was obtained by distributing questionnaires directly to consumer respondents using Shopee in Sukabumi City using Google Forms. The analytical tool used in this study is multiple linear regression. The results of this study showed that mobile marketing variables have a positive influence on customer engagement, content marketing variables have a positive influence on customer engagement, and there is a positive influence of mobile marketing and content marketing variables on customer engagement, with an influence of 50% while 50% is influenced by other variables that are not studied. The contribution of this research is to expand marketing management literature on mobile marketing, content marketing, and customer engagement in the context of marketing.